Preclinical assessment of a new recombinant ADAMTS‐13 drug product (BAX930) for the treatment of thrombotic thrombocytopenic purpura. (2nd July 2016) - Kopić, A.; Benamara, K.; Piskernik, C.; Plaimauer, B.; Horling, F.; Höbarth, G.; Ruthsatz, T.; Dietrich, B.; Muchitsch, E.‐M.; Scheiflinger, F.; Turecek, M.; Höllriegl, W.
Abstract : Essentials ADAMTS‐13‐deficiency is a cause of thrombotic thrombocytopenic purpura (TTP). Preclinical safety of recombinant human ADAMTS‐13 (BAX930) was shown in animal models. Preclinical efficacy of BAX930 was shown in a mouse model of TTP. BAX930 showed advantageous efficacy over fresh frozen plasma, the current standard of care. Click to hear Dr Cataland and Prof. Lämmle present a seminar on Thrombotic Thrombocytopenic Purpura (TTP): new Insights in Pathogenesis and Treatment Modalities . Summary: Background: Thrombotic thrombocytopenic purpura (TTP) is a rare blood disorder characterized by microthrombosis in small blood vessels of the body, resulting in a low platelet count. Baxalta has developed a new recombinant ADAMTS‐13 (rADAMTS‐13) product (BAX930) for on‐demand and prophylactic treatment of patients with hereditary TTP (hTTP). Objectives: To evaluate the pharmacokinetics, efficacy and safety of BAX930 in different species, by use of an extensive preclinical program. Methods: The prophylactic and therapeutic efficacies of BAX930 were tested in a previously established TTP mouse model. Pharmacokinetics were evaluated after single intravenous bolus injection in mice and rats, and after repeated dosing in cynomolgus monkeys. Toxicity was assessed in rats and monkeys, safety pharmacology in monkeys, and local tolerance in rabbits. Results: BAX930 was shown to be efficacious, as demonstrated by a stabilized platelet count in ADAMTS‐13 knockout mice that were thrombocytopenic when treated. Prophylactic efficacy was dose‐dependent and comparable with that achieved by treatment with fresh frozen plasma, the mainstay of hTTP treatment. Therapeutic efficacy was treatment interval‐dependent. Safety pharmacology evaluation did not show any deleterious effects of BAX930 on cardiovascular and respiratory functions in monkeys. The compound's pharmacokinetics were similar and dose‐proportional in mice, rats, and monkeys. BAX930 was well tolerated in rats, monkeys, and rabbits, even at the highest doses tested. Conclusions: These results demonstrate that BAX930 has a favorable preclinical profile, and support the clinical development of rADAMTS‐13 for the treatment of hTTP.